Інструменти інформаційної кампанії Камали Гарріс під час президентських виборів 2024 року: стратегії та тактики політичної комунікації - Юрченко, Ольга; Луценко, Софія (Видавництво Львівської політехніки, 2025)
This paper examines the key tools and strategies employed by Kamala Harris during her 2024 presidential campaign. It explores using digital media, social platforms, and targeted communication to activate voters, particularly among young people and marginalized communities. The campaign's reliance on high-profile endorsements, including Oprah Winfrey, Elizabeth Warren, Beyoncé, Kerry Washington, and Taylor Swift etc., significantly shaped public perception and drove voter engagement. These influencers were pivotal in creating emotional connections and promoting Harris's progressive platform.
Keywords: Камала Гарріс; президентські вибори 2024; інформаційні кампанії; політична комунікація; цифрові медіа; підтримка інфлюенсерів